Benign ovarian neoplasm in adolescence. - Castellano, Carlos (2015)
Although ovarian tumors account for no more than 1% of all neoplasms in the girls under 16 years, they are, however, more common in that period of life genital tumor. Despite their rarity, they should be kept in mind in the differential diagnosis of many abdominal disorders. Because of its rarity, sometimes they undiagnosed and can lead to special problems. Any type of ovarian tumor seen in adult women, has also been found in girls. Approximately 30% of all ovarian tumors in children and adolescents are teratomas or dermoid cyst; moiety includes all kinds of benign and malignant tumors.